KONSENTRASI DAN FREKUENSI PEMBERIAN PUPUK MAJEMUK BERTEKNOLOGI NANO UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL PANEN TANAMAN OKRA (Abelmoschus esculentus) - Setya Wibowo, Agung; Endrawati, Tri; Sarjani, Alvita; Puspitorini, Palupi (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2023)
Okra (Abelmoschus esculentus) is a tropical vegetable with numerous benefits that can adapt to tropical climates. Meeting the demand for okra requires a technological package to enhance its crop yield. One approach to improving okra yield involves the use of economically efficient nano-technology compound fertilizers, which enhance nutrient absorption by plants through direct nutrient release absorbed by the plant roots. This research aims to investigate the interaction between the concentration and frequency of nano-technology compound fertilizer application on the growth and yield of red okra (Abelmoschus esculentus). The study employs a two-factor randomized block design. The first factor involves different concentrations of nano-technology compound fertilizer with four treatments: P1: 2 ml/L, P2: 4 ml/L, P3: 6 ml/L, and P4: 8 ml/L. The second factor pertains to the frequency of nano-technology compound fertilizer application with three treatments: S1: Irrigation once a week, S2: Irrigation twice a week, and S3: Irrigation thrice a week. Each treatment consists of three replications. Observational variables include plant height, leaf count, stem diameter, flower count, fruit count, fruit diameter, fruit length, and fruit weight. The results of this research: application of nano-technology compound fertilizer at a concentration of 2 ml/L with a frequency of thrice a week significantly promotes the growth in plant height and stem diameter of okra. Furthermore, the application of nano-technology compound fertilizer at a concentration of 6 ml/L with a frequency of thrice a week significantly influences fruit diameter, fruit length, and fruit weight in okra plants.